Measuring Crime Rates of Prisoners in Colorado, 1988-1989 - English, Kim ([Verlag nicht ermittelbar], 1997)
In the late 1970s, the Rand Corporation pioneered a method of collecting crime rate statistics. They obtained reports of offending behavior--types and frequencies of crimes committed--directly from offenders serving prison sentences. The current study extends this research by exploring the extent to which variation in the methodological approach affects prisoners' self-reports of criminal activity. If the crime rates reported in this survey remained constant across methods, perhaps one of the new techniques developed would be easier and/or less expensive to administer. Also, the self-reported offending rate data for female offenders in this collection represents the first time such data has been collected for females. Male and female prisoners recently admitted to the Diagnostic Unit of the Colorado Department of Corrections were selected for participation in the study. Prisoners were given one of two different survey instruments, referred to as the long form and short form. Both questionnaires dealt with the number of times respondents committed each of eight types of crimes during a 12-month measurement period. The crimes of interest were burglary, robbery, assault, theft, auto theft, forgery/credit card and check-writing crimes, fraud, and drug dealing. The long form of the instrument focused on juvenile and adult criminal activity and covered the offender's childhood and family. It also contained questions about the offender's rap sheet as one of the bases for validating the self-reported data. The crime count sections of the long form contained questions about motivation, initiative, whether the offender usually acted alone or with others, and if the crimes recorded included crimes against people he or she knew. Long-form data are given in Part 1. The short form of the survey had fewer or no questions compared with the long form on areas such as the respondent's rap sheet, the number of crimes committed as a juvenile, the number of times the respondent was on probation or parole, the respondent's childhood experiences, and the respondent's perception of his criminal career. These data are contained in Part 2. In addition, the surveys were administered under different conditions of confidentiality. Prisoners given what were called "confidential" interviews had their names identified with the survey. Those interviewed under conditions of anonymity did not have their names associated with the survey. The short forms were all administered anonymously, while the long forms were either anonymous or confidential. In addition to the surveys, data were collected from official records, which are presented in Part 3. The official record data collection form was designed to collect detailed criminal history information, particularly during the measurement period identified in the questionnaires, plus a number of demographic and drug-use items. This information, when compared with the self-reported offense data from the measurement period in both the short and long forms, allows a validity analysis to be performed.